2015
DOI: 10.1002/2015ms000478
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of high‐level clouds in cloud resolving model simulations with ARM and KWAJEX observations

Abstract: In this study, we evaluate high-level clouds in a cloud resolving model during two convective cases, ARM9707 and KWAJEX. The simulated joint histograms of cloud occurrence and radar reflectivity compare well with cloud radar and satellite observations when using a two-moment microphysics scheme. However, simulations performed with a single moment microphysical scheme exhibit low biases of approximately 20 dB. During convective events, two-moment microphysical overestimate the amount of high-level cloud and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The overprediction of high cloud and excessive upper level humidity (as we also find here) has been recognized in other MMF studies [ McFarlane et al ., ; Zhang et al ., ]. It has been suggested that this is related to the overestimation of vertical transport of humidity [ Zhang et al ., ], the adoption of periodic lateral boundary conditions in the cloud‐resolved model embedded in MMF [ Luo and Stephens , ; Liu et al ., ], and problems with the parameterization of the ice cloud microphysics [ Khairoutdinov et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…The overprediction of high cloud and excessive upper level humidity (as we also find here) has been recognized in other MMF studies [ McFarlane et al ., ; Zhang et al ., ]. It has been suggested that this is related to the overestimation of vertical transport of humidity [ Zhang et al ., ], the adoption of periodic lateral boundary conditions in the cloud‐resolved model embedded in MMF [ Luo and Stephens , ; Liu et al ., ], and problems with the parameterization of the ice cloud microphysics [ Khairoutdinov et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent work (Sun & Pritchard, ) we showed that the use of Superparameterization (SP) in the SP version of the Community Atmosphere Model (SPCAM), which uses an embedded cloud resolving model within each GCM grid column to replace typical parameterizations of moist convection and vertical mixing, simulates more realistically damped coupling signals in the water pathway of the land‐atmosphere feedback loop compared to its counterpart (i.e., regular Community Atmosphere Model). Some studies examined the effects of superparameterization on cloud properties and shown that in some regimes SPCAM can offer improvements in cloud cover (Marchand & Ackerman, ) and high‐level cloud amount (Liu et al, ), albeit to different degrees depending on model configuration or microphysics scheme. Such cloud properties directly affect atmospheric radiative transfer and thus the energy budget at the land surface.…”
Section: Introductionmentioning
confidence: 99%
“…The only variable that exhibited a noticeable sensitivity to the microphysics scheme was the column water vapor, where the P3 scheme demonstrated a stronger correlation with the observations. Compared with previous work addressing the model sensitivity to microphysics, model domain, and resolution (KHAIROUTDINOV; RANDALL, 2003;KHAIROUTDINOV;RANDALL, 2006;BLOSSEY et al, 2007;KHAIROUTDINOV et al, 2009;HENDERSON;PINCUS, 2009;LIU;MUHLBAUER;ACKERMAN, 2015;BLOSSEY;MOHRMANN, 2021), this thesis focused specifically on the Amazon region and considered the calculation of surface fluxes through the SLM. Although the recent work by GONÇALVES et al (2022) employed the GoAmazon2014/5 observations, they did not assess the evolution of moisture content and surface latent and sensible heat fluxes.…”
Section: Discussionmentioning
confidence: 99%